USE OF INTERNET RESOURCES IN FUTURE TEACHERS' PROFESSIONAL TRAINING IN THE DISTANCE LEARNING CONDITIONS - Tsiuniak, Oksana; Fedirchyk, Tetiana; Nikula, Natalia (Mountain School of Ukrainian Carpaty, 2021)
The article substantiates the urgency of future teachers professional training problem in distance learning conditions, as well as the need for education digital transformation, educational process organization the with the introduction of innovative and digital technologies. It was found that the informatization of modern society contributes to the popularization of Internet resources used in the educational process of higher education institutions. It is substantiated that the modern teacher should navigate in the information space, receive information, which is the main resource of digital education, and operate it in accordance with their own needs and requirements of professional activity; use Internet technologies, local networks; develop their own electronic products; must acquire new knowledge and skills that will help to work comfortably and be competitive in the educational space of the information society. It should be noted that usage of personal educational web resources can significantly increase the efficiency of the educational process, intensify educational-cognitive and independent activities the applicants for higher education and organize quality training in distance learning conditions. It should be noted that usage of personal educational web resources can significantly increase the efficiency of the educational process, intensify educational-cognitive and independent activities the applicants for higher education and organize quality training in distance learning conditions.